BIOMETRIC TECHNOLOGIES AS A PERSPECTIVE DIRECTION OF IMPROVING REMOTE BANK SERVICE - E. I. Shamanina; Yu. S. Zakharenko (Вестник университета)
The issues related to the developing and improving remote identification mechanism in the Russian banking sector have been considered. The main aspects of the process of collecting, processing, checking and storing biometric data, the functioning status of Single Biometric System (SBS) have been highlighted. The vulnerability and risks of using biometric technologies by banks have been noted. The key trends in the development of the international market of biometric technologies and their application in the banking sector have been presented, as well as current events on the implementation of biometric technologies in Russia. The prospects for the use of biometric technologies in the banking sector and directions for improving the technological infrastructure in order to protect data from unauthorized access have been outlined.